Essays on social responsibility in the marketplace : an experimental economic analysis - Wang, Yan (2018)
The idea of market exchange dates back to the ancient world, as evidenced, for example, by ancient bazaars. Over the years, along with the development of the market economy, there have been many cases where sellers or buyers do not take responsibility for external costs generated by their activities, and these costs have instead been passed on to society. A voluntary market exchange would generally generate a social gain, on the condition that there are no negative externalities, whereas production or consumption of goods and services with negative externalities would potentially cause a social loss. Increasing attention has, therefore, been paid to correcting market failure from negative externalities. There are a lot of interventions that are adopted by governments to address the issue of negative externalities, for example, imposing taxes and making laws or regulations. Apart from the driving forces of governments, the society can also take part in the stimulation of social responsibility. Promoting socially responsible behaviors has recently been recognized as a powerful approach that internalizes negative externalities. In particular, negative externalities caused by insufficient social responsibility have become an increasing concern, which further highlights the importance of stimulating social responsibility. This thesis is concerned with socially responsible behaviors in the marketplace. We delve into this issue by investigating several potential interventions that stimulate socially responsible behaviors in a market setting. The thesis consists of three self-contained essays. Chapter 1 investigates the role of non-binding social persuasion in motivating socially responsible behaviors in markets with negative externalities imposed on uninvolved third parties. In our study, we vary the costs of engaging in socially responsible behavior and investigate what influences the increase in these costs have on the incentives for sellers and buyers to act in a socially responsible manner and the effectiveness of social persuasion. We show that social persuasion can indeed promote socially responsible behavior by influencing the attitudes of both sellers and buyers. Chapter 2 reports the results of an experiment designed to explore the sanctioning behavior of third parties and its impact on socially responsible production and consumption when third parties are adversely affected by socially irresponsible transactions. Within our study, we introduce a third party voluntary contribution mechanism with opportunities to punish socially irresponsible sellers. Meanwhile, we also vary the costs of conducting socially responsible behaviors. The responses of sellers and the behavioral change of buyers are subsequently examined. We find that sanctions exert a positive impact on socially responsible production but conversely, diminish the impulses towards socially responsible behavior in buyers. Chapter 3 explores the causality between buyers’ ex-ante product preferences and socially responsible production. We disclose consumer product preferences to firms before firms make production decisions. Our results demonstrate that a knowledge of buyers’ preferences for socially responsible products would encourage sellers to exhibit social responsibility, on the condition that the preference is strong enough. However, the disclosure of the preference also causes a price reduction in socially irresponsible products. Attracted by the lower price, some buyers will switch to socially irresponsible products, a factor that, therefore, counteracts the positive influence of understanding buyers’ preferences.